Investigation of the I–V characteristics of n+/n homojunctions introduced by heavy ion irradiation in CdZnTe crystals. Issue 8 (2nd February 2023) - Liang, Lu; Wang, Aoqiu; Wang, Yingming; Qin, Zhentao; Qin, Chi; Shang, Rongjin; Jiang, Kai; Cao, Yuwei; Xu, Lingyan; Jie, Wanqi
Abstract : The current transport of CdZnTe crystals follows the Schottky emission model due to n + /n homojunctions introduced by heavy ion irradiation. Abstract : Understanding the effects of heavy ion irradiation is significant for materials and devices applied in the field of nuclear radiation detection. In this paper, the relationship between heavy ions (20 MeV Cl) and electric performance in CdZnTe crystals has been investigated. A damage layer is introduced 6 μm below the CdZnTe crystal surface and dominated by donor defects according to the SRIM (stopping and range of ions in matter) calculation and Hall effect results. The current–voltage ( I – V ) is asymmetrical, which is attributed to the n + /n homojunction formed by the damage layer. The barrier height of the homojunction increases from 0.845 to 0.946 eV with radiation fluence. For low irradiation fluences, the I – V curves follow the Schottky emission model at a bias of 0–100 V because of barrier lowering due to the applied field and the image force. When the irradiation fluence is greater than 2.5 × 10 12 n cm −2, the increasing leakage current after 40 V voltage conforms to the Poole–Frenkel (PF) effect caused by deep traps. The carrier mobility largely decreases from ∼1100 cm 2 V −1 s −1 to 267–658 cm 2 V −1 s −1 due to the scattering of ionized impurities. The energy resolving capability of γ-rays deteriorates from ∼8% to 15.3–26.8% by the trapping effect. The photopeak of the γ spectrum could not be recognized when the fluence reached 1.4 × 10 13 n cm −2 . This work provides important irradiation protection reference data for CdZnTe devices in various high-fluence application fields, such as industrial monitoring and nuclear spectroscopy.